Ustekinumab Treatment of Erythrodermic Psoriasis Occurring after Physical Stress: A Report of Two Cases - Rosita Saraceno; Marina Talamonti; Marco Galluzzo; Andrea Chiricozzi; Antonio Costanzo; Sergio Chimenti (Karger Publishers, 2013)
Erythrodermic psoriasis (EP) is a severe form of psoriasis precipitated by numerous factors, including physical stress, infections, and drugs. The disease represents a therapeutic challenge, and little is known about its response to ustekinumab. Though the efficacy of ustekinumab has been extensively studied in chronic plaque psoriasis, no trials have been carried out in EP. We report the case of 2 patients, 1 male and 1 female, who showed EP despite being treated with etanercept and methotrexate for chronic plaque psoriasis, respectively. The patients were treated with ustekinumab at a dosage of 45 mg s.c. They showed a significant improvement in their Psoriasis Area and Severity Index score after only 4 weeks of ustekinumab therapy, and further improvements were observed throughout the treatment. In our experience, ustekinumab has been proven safe and effective, without increasing the dosage, in controlling and preventing the occurrence of erythrodermic flares. Ustekinumab therapy may therefore be considered a valid therapeutic option for the treatment of EP, even in cases where other biological agents have failed.